Enhancing the 21st century learning through the flipped classroom approach: A science teacher's perspectives - Mohd Fadzly Wasriep; Denis Andrew D. Lajium (Readers Insight Publisher, 2019)
A flip classroom is closely related to the inverted classroom that promotes learning outside the classroom (Lage et al., 2000). The main reason for the implementation of the flipped classroom is to free up the allotted learning time at school so that more engaging activities could be done (Milman, 2014). Since the flipped classroom is still at its early phase in Malaysia, there are limited studies done in this area (A. Rahman, Abdullah, Mohammed, Mohd Zaid, & Aris, 2014). This preliminary study reveals three issues in 21st-century learning experience via primary science flipped classroom implementations including the affordances, assistance and challenges. There are various aspects taken into consideration from the teacher and teaching surrounding for the flipped classroom settings to be conducive. The teacher realized that although flipped classroom helped her in some ways nonetheless there are challenges that she has to resolve.